A Multistep Method for Automatic Determination and Optimization of Microseismic P-Phase Arrival Times in a Coal Mine. (19th June 2019) - Zhu, Quanjie; Liu, Xiaohui; Liu, Xiaoyun; Chai, Haitao; Shi, Jianjun
Abstract : We present an algorithm for P-phase arrival time automatic determination and optimization for microseismic events of a coal mine in steps. For P-phase detection, we apply four modules: single denoising (band-filter), fast searching (STA/LTA and peak value), accurately picking (AIC), and optimization selection (time difference of arrival time and envelope circle judgment). This method is applied for a precise determination of P-phase arrival time; in addition, an automatic quality estimate is obtained to optimize and select the effective stations and used for source location. Through the analysis and validation of seismic data in a mine located in Hebei province, the result shows that this method can pick up the first arrival time of MS signal fast and accurately and automatically judge and remove the error station. Comparing automatic picks with the manual method in terms of speed and accuracy, computation cost (0.828 s) is far less than manual method (15 s per set), precision of manual and automatic represented by picking error is up to 71.7% (between −5 ms and 5 ms, 190 sets), 83.4% (between −10 ms and 10 ms, 221 sets), and 90.57% (between −20 ms and 20 ms, 240 sets). This study shows that the method presented in this paper is feasible to precise automatic P-phase determination and is a basis on automatic and precision location.